Empowerment Through Patient Education - Hughes, Carson (My University, 2024)
This project analyzes the effectiveness of a mnemonic tool designed to enhance healthcare providers' ability to deliver health education while establishing trusting patient-provider relationships to improve patient education.
Keywords: Empowerment, Education, Health